PROCEDURE FOR COLLECTION OF RECEIVABLES WITH RECEIVABLES BILL AT PT INTEGRASI PRODUKTIVITAS INDONESIA - Pratiwi, Esti Utami; Fikri, Ahmad Rijalul (Review of Accounting and Taxation, 2023)
Purpose - The purpose of this Final Project Research is to find out the process of making Receivables Collection Procedures with Receivables Bill at PT Integrasi Productivity Indonesia. The method used in this study is qualitative descriptive. Design/methodology/approach - The techniques used in collecting the data obtained are primary data and secondary data. Finding - PT Integrasi Productivity Indonesia as a company engaged in services really needs a Receivables Collection Procedure. With the establishment of Receivables Collection Procedures, it can help minimize the occurrence of payment delays by customers that cause bad debts, especially at PT Integrasi Productivity Indonesia. With the information obtained from this Receivables Collection Procedure, financial staff can carry out receivables collection better by using the procedures that have been made. Originality -